GENETIC SUSCEPTIBILITY OF TRANSCRIPTION FACTOR 7-LIKE 2 GENE VARIANT AND RISK OF TYPE 2 DIABETES IN ASIAN INDIANS - NAVNEET KAUR; GURJIT KAUR BHATTI; SANJAY KUMAR BHADADA; SAMER SINGH; JASVINDER SINGH BHATTI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Background: The variants of transcription factor 7-like 2 (TCF7L2) gene have been shown to be associated with type 2 diabetes mellitus (T2DM) and its related complications. Objectives: We aimed to explore the possible association of rs7903146 (C/T) variant in TCF7L2 with the risk of T2DM in the North Indian population. Methods: The present case–control study included a total of 638 human subjects (318 T2DM subjects and 320 healthy controls). Various anthropometric, biochemical, and genetic parameters were studies in all the subjects. Genotyping of TCF7L2 gene was carried out using allele-specific polymerase chain reaction method. Results: The results of this study indicate significantly higher values of body mass index, waist circumference, waist-to-hip ratio, and body fat (%) in T2DM subjects than controls (p≤0.001). Dyslipidemia represented by higher levels of triglycerides and reduced values of high-density lipoprotein was more predominant in diabetic subjects compared to healthy subjects. The frequency of risk genotype (TT) frequency was significantly higher in T2DM subjects (16.4%) compared to controls (11.6%). The “T” allele was more dominant in diabetic subjects than controls. Logistic regression analysis of the data revealed a significant association of TT genotype with 2-fold (odds ratio with 95% of confidence interval; 2.09 [1.29–3.42] p=0.003) and CT genotype with 1.7-fold (1.73 [1.23–2.44] p=0.002) increased risk of developing T2DM. Conclusions: The present study demonstrated a significant association of rs7903146 (C/T) variant in TCF7L2 with the augmented risk of T2DM in North Indian population.